Using blue whale (Balaenoptera musculus) photographic-identiﬁcation sightings to assess potential vessel-whale encounters in the Santa Barbara Channel - Stingle, Kelli Faye (2012)
In 2007 six blue whales (Balaenoptera musculus) were found dead in the Southern California Bight with four of the deaths resulting from vessel strikes. To reduce the spatial overlap of vessels and whales, the United States Coast Guard proposed shifting the southern Santa Barbara Channel shipping lane north by one nmi. We used sighting rate predictions from generalized additive models to assess potential vessel-whale encounters in the current and proposed traffic separation schemes. Sightings were collected during coastal-based photo-identiﬁcation surveys between June - November from 2001 to 2009. In total, 11,037 km of track-line was searched, yielding 602 sightings of 393 uniquely identiﬁed blue whales. Whales were strongly associated with spatial covariates and bathymetric features, with the highest sighting rates predicted in close proximity to the shelf edge on steep south facing slopes and shallow northeast facing slopes. The proposed traffic separation scheme could reduce potential vessel-whale encounters by 15%.